Critical literacy and self-identity: narratives of incarcerated female adolescents - Omar, Noritah (Universiti Putra Malaysia Press, 2019)
This book spotlights incarceration as an act of “compassionate intention” for juveniles. It narrates in detail a doctoral study which used narrative inquiry to investigate the construction of self-identity by incarcerated female adolescents involved in a story-telling program in a juvenile detention facility. A combination of critical theory, feminism, and the Islamic religious views of the researcher served as the theoretical and methodological foundation of the study. The study highlights how the social and institutional surveillance which constantly framed the lives of these incarcerated adolescents tended to preserve their low sense of status and to undermine their sense of intellectuality. The study also shows how the participants’ self-identity constructions can be directly associated with critical literacy, thus providing a means for empowerment through narrative as a form of self-inquiry, a stage for confrontation, and a channel for personal revelations.